CFD analysis of phase holdup behaviour in a gas-liquid bubble column - Abd Halim, Nur Khairunnisa; Hussain, Siti Aslina; Abd. Razak, Mus’ab; Mohd Yunos, Mohd Amirul Syafiq (Faculty of Engineering Universiti Malaysia Sarawak, 2021)
Experimental works on bubble column hydrodynamic are normally carried out on a laboratory scale less than 0.3 m with holes number less than 10. In this paper, we discuss several approaches to bubble column scale-up, relying on variables of parameters. Two spargers with different hole diameters (0.5 mm and 1.25 mm) and superficial gas velocities (0.0125 m/s and 0.0501 m/s) are used to determine the distribution of gas holdup and liquid flow pattern. An Insignificant level of bed heights is investigated for the efficiency of hydrodynamic performance. Computational Fluid Dynamic (CFD) is used as the realistic representation of the actual reactor. The flow of the gas-liquid interface is implemented using the VOF model using the finite volume method by tracking the volume fraction of each of the fluids throughout the domain. It is observed that the initial bed heights, superficial gas velocity, and hole diameter of the sparger influence the overall gas holdup. Although the difference in sparger hole diameter affects overall gas holdup, the results are weak relative to other operating conditions. The simulation work is then compared with experimental data to improve the accuracy in analyzing the hydrodynamics of multiphase system, as well as validated the multidimensional models.